2019
DOI: 10.1002/hep.30312
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Entecavir/Peginterferon Alfa‐2a in Children With Hepatitis B e Antigen–Positive Immune Tolerant Chronic Hepatitis B Virus Infection

Abstract: The optimal management strategy for children with immune‐tolerant chronic hepatitis B virus (HBV) infection remains unknown. The purpose of this clinical trial was to determine the safety and efficacy of therapy with entecavir and peginterferon in a group of children in the immune‐tolerant phase of HBV infection. Children with immune‐tolerant features of chronic hepatitis B (CHB) received entecavir once‐daily in a dose of 0.015 mg/kg (0.5 mg maximum) for 48 weeks; peginterferon alfa‐2a (180 µg/1.73m2 subcutane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
3
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 23 publications
5
52
3
3
Order By: Relevance
“…(3) In the current issue, Rosenthal et al report a study of entecavir administered for an initial 8 weeks with the addition of pegylated interferon for the subsequent 40 weeks in 60 children with IT chronic HBV. (4) Disappointingly, only 2 (3%) reached the primary endpoint of HBeAg loss and durable HBV DNA suppression ≤1,000 IU/ mL, although both also lost HBsAg. Two additional children also cleared HBeAg but did not return for their final study visit, so it is possible that they also met the study endpoints.…”
Section: See Articles On Pages 2326 and 2338mentioning
confidence: 97%
See 1 more Smart Citation
“…(3) In the current issue, Rosenthal et al report a study of entecavir administered for an initial 8 weeks with the addition of pegylated interferon for the subsequent 40 weeks in 60 children with IT chronic HBV. (4) Disappointingly, only 2 (3%) reached the primary endpoint of HBeAg loss and durable HBV DNA suppression ≤1,000 IU/ mL, although both also lost HBsAg. Two additional children also cleared HBeAg but did not return for their final study visit, so it is possible that they also met the study endpoints.…”
Section: See Articles On Pages 2326 and 2338mentioning
confidence: 97%
“…Poddar et al reported similarly encouraging results using the same combination regimen in 24 IT children with chronic HBV . In the current issue, Rosenthal et al report a study of entecavir administered for an initial 8 weeks with the addition of pegylated interferon for the subsequent 40 weeks in 60 children with IT chronic HBV . Disappointingly, only 2 (3%) reached the primary endpoint of HBeAg loss and durable HBV DNA suppression ≤1,000 IU/mL, although both also lost HBsAg.…”
mentioning
confidence: 99%
“…23,30 Pegylatedinterferon (PEG-IFN) and NAs inhibit HBV replication, but they do not eradicate HBV and rarely achieve the goal of HBsAg clearance. 31 Chan et al 32 studied 126 adults with IT HBV who received tenofovir disoproxil fumarate with or without 33 found only a 3% response rate in IT children treated with PEG-IFN and entecavir. Viral relapse occurred in all patients when treatment was stopped and was not accompanied by ALT flares.…”
Section: Limitations Of Current Treatmentsmentioning
confidence: 99%
“…Rosenthal et al publizierten aktuell eine klinische Studie ebenfalls mit Peginterferon-α2a in Kombination mit Entecavir und erreichten den primären Endpunkt, die anti-HBe-Serokonversion nach 48 Wochen, nur bei 3 % der behandelten Kinder. Daher wird eine Therapie in der immuntoleranten Phase weiterhin nicht empfohlen [15].…”
Section: Chronische Hepatitis Bunclassified